Sequential versus simultaneous presentation of memoranda in verbal working memory: (How) does it matter? - Ordonez Magro, Laura; Mirault, Jonathan; Grainger, Jonathan; Majerus, Steve (Memory & Cognition, 2022)
To-be-memorized information in verbal working memory (WM) can be presented sequentially, like in oral language, and simultaneously, like in written language. Few studies have addressed the importance and implications for verbal WM processing of these two presentation modes. While sequential presentation may favor discrete, temporal encoding processes, simultaneous presentation may favor spatial encoding processes. We compared immediate serial recall tasks for sequential versus simultaneous word list presentation with a specific focus on serial position curves of recall performance, transposition gradients, and the nature of serial order errors. First, we observed higher recall performance in the simultaneous compared to the sequential conditions, with a particularly large effect at end-of-list items. Moreover, results showed more transposition errors between non-adjacent items for the sequential condition, as well as more omission errors especially for start-of-list items. This observation can be explained in terms of differences in refreshing opportunities for start-of-list items during encoding between conditions. This study shows that the presentation mode of sequential material can have a significant impact on verbal WM performance, with an advantage for simultaneous encoding of sequence information.